Vitamin D and rheumatic diseases - M. Rossini (Reumatismo, 2014)
Vitamin D has some well-known effects on calcium, phosphate and bone metabolism, but it has recently shown to have many other effects, which may potentially be relevant to patients with extra-skeletal rheumatic diseases. Such effects may be justified by: 1) the presence of the vitamin D receptors also on extra-osseous cells, such as cartilage cells, sinoviocytes, muscle cells; 2) the proven role of vitamin D in the control of the transcription of genes involved in rheumatic diseases; 3) the evidence that vitamin D has multiple endocrine effects not only on calcium homeostasis; 4) the activation of vitamin D not only in the kidneys, but also in monocyte-macrophage and lymphocytic cell lines and in some epithelial cells with additional intracrine and paracrine effects. Vitamin D deficiency has been reported in numerous metabolic, degenerative, inflammatory and autoimmune rheumatic diseases. In some cases this association was also related to the risk of developing a rheumatic disease or the degree of disease activity. However there is no conclusive evidence of the efficacy of a preventive or therapeutic strategy based on vitamin D supplementation in extra-skeletal rheumatic diseases. This review aims to provide an overview of the latest evidence concerning the relationship between vitamin D and the most relevant rheumatic diseases.